Simulation of Three-Dimensional Strained Heteroepitaxial Growth Using Kinetic Monte Carlo (Communications in Computational Physics, 2011)
Efficient algorithms for the simulation of strained heteroepitaxial growthwith intermixing in 2+1 dimensions are presented. The first of these algorithms is anextension of the energy localization method [T. P. Schulze and P. Smereka, An energylocalization principle and its application to fast kinetic Monte Carlo simulation of heteroepitaxialgrowth, J. Mech. Phys. Sol., 3 (2009), 521–538] from 1+1 to 2+1 dimensions.Two approximations of this basic algorithm are then introduced, one of which treatsadatoms in a more efficient manner, while the other makes use of an approximationof the change in elastic energy in terms of local elastic energy density. In both cases,it is demonstrated that a reasonable level of fidelity is achieved. Results are presentedshowing how the film morphology is affected by misfit and deposition rate. In addition,simulations of stacked quantum dots are also presented.